THE DYNAMIC EQUATION OF ACCOUNTING. - Lipkin, Lawrence (The Accounting Review, 1959)
This article says that the equation A = L+P is often termed the basic of fundamental equation of accounting. There is no question as to the validity of this equation. There is, however, a question as to whether or not this equation should be termed the basic equation of accounting, implying that it fully describes the accounting and economic processes of the firm. A much more useful equation to describe the accounting process and accounting relationships can be readily developed wherein it is not necessary to qualify P by definition, implication, or otherwise. This dynamic equation can be extremely useful in teaching elementary accounting, for the instructor can explain much theory and some of the mechanics of accounting quite easily with the help of this equation. Another excellent use of the dynamic equation is in explaining the theory of closing the books. All too often this becomes a rather mechanical process for the student doesn't really understand what he is trying to accomplish. It can also be pointed out that the dynamic equation represents the general ledger because it includes all categories of accounts.